Mesogenic Groups Control the Emitter Orientation in Multi‐Resonance TADF Emitter Films. (8th March 2023) - Chen, Dongyang; Tenopala‐Carmona, Francisco; Knöller, Julius A.; Mischok, Andreas; Hall, David; Madayanad Suresh, Subeesh; Matulaitis, Tomas; Olivier, Yoann; Nacke, Pierre; Gießelmann, Frank; Laschat, Sabine; Gather, Malte C.; et al.
Abstract: The use of thermally activated delayed fluorescence (TADF) emitters and emitters that show preferential horizontal orientation of their transition dipole moment (TDM) are two emerging strategies to enhance the efficiency of OLEDs. We present the first example of a liquid crystalline multi‐resonance TADF (MR‐TADF) emitter, DiKTa‐LC . The compound possesses a nematic liquid crystalline phase between 80 °C and 110 °C. Importantly, the TDM of the spin‐coated film shows preferential horizontal orientation, with an anisotropy factor, a, of 0.28, which is preserved in doped poly(vinylcarbazole) films. Green‐emitting ( λ EL =492 nm) solution‐processed OLEDs based on DiKTa‐LC showed an EQEmax of 13.6 %. We thus demonstrate for the first time how self‐assembly of a liquid crystalline TADF emitter can lead to the so‐far elusive control of the orientation of the transition dipole in solution‐processed films, which will be of relevance for high‐performance solution‐processed OLEDs. Abstract : Our work shows how the distinct self‐assembly of a liquid crystalline MR‐TADF emitter can be exploited for generating (partially) aligned via solution‐processed thin films – an advance towards high performance solution‐processable organic semiconductors.